Examining Script Evolution through Language Contact: The Case of Naxi Manuscripts and Chinese Characters - Dai, Antong; Lin, Ziqing (Journal Corner of Education, Linguistics, and Literature, 2025)
This study explored the impact of language contact on written languages through the case study of Chinese character borrowing in Naxi Manuscripts. Drawing from four primary corpora spanning religious, medical, and divinatory genres, the study identifies 11 frequently borrowed Chinese characters and 301 instances of borrowing through a combination of optical character recognition (OCR) and manual verification. The borrowing is in three types: phonetic, semantic, and graphic borrowing. Through two proposed indicators,  "Borrowing Breadth" and "Borrowing Density", the study quantifies the extent of borrowing for different genres. Results show that medical texts exhibit the highest level of Chinese character borrowing, reflecting the extensive interaction between Naxi and Han in this field. In contrast, religious texts display the lowest borrowing rate, possibly due to their earlier composition and limited cross-cultural contact at the time. Phonetic borrowings and semantic borrowings significantly outnumber graphic borrowings, revealing that the functional features of characters were prioritized over their abstract visual forms. This paper not only expands the research on the language contact between Naxi and Han but also shows the important role of genres in linguistic integration and exemplifies how language contact can lead to script evolution.